2017
DOI: 10.1038/s41598-017-15039-8
|View full text |Cite
|
Sign up to set email alerts
|

A Zika Vaccine Targeting NS1 Protein Protects Immunocompetent Adult Mice in a Lethal Challenge Model

Abstract: Zika virus (ZIKV) is a mosquito-borne flavivirus that has rapidly extended its geographic range around the world. Its association with abnormal fetal brain development, sexual transmission, and lack of a preventive vaccine have constituted a global health concern. Designing a safe and effective vaccine requires significant caution due to overlapping geographical distribution of ZIKV with dengue virus (DENV) and other flaviviruses, possibly resulting in more severe disease manifestations in flavivirus immune va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 40 publications
(38 reference statements)
5
86
1
9
Order By: Relevance
“…These studies highlight the value of including the NS1 protein in candidate vaccines for flaviviruses. During revision of our manuscript, Brault et al reported that intramuscular immunization of immunocompetent mice with the Modified Vaccinia Ankara (MVA) vector expressing NS1 (MVA-ZIKV-NS1) vaccine candidate provided 100% protection against a lethal intracerebral dose of ZIKV (strain MR766) 61 . However, their study did not evaluate the efficacy of MVA-ZIKV-NS1 in A129 mice which is more highly sensitive to ZIKV infection.…”
Section: Discussionmentioning
confidence: 99%
“…These studies highlight the value of including the NS1 protein in candidate vaccines for flaviviruses. During revision of our manuscript, Brault et al reported that intramuscular immunization of immunocompetent mice with the Modified Vaccinia Ankara (MVA) vector expressing NS1 (MVA-ZIKV-NS1) vaccine candidate provided 100% protection against a lethal intracerebral dose of ZIKV (strain MR766) 61 . However, their study did not evaluate the efficacy of MVA-ZIKV-NS1 in A129 mice which is more highly sensitive to ZIKV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, MVA and MV vectors have been engineered to express the NS1 or prM-ENV proteins of ZIKV, respectively. Protection in pre-clinical models with these candidates has also been reported 73 .…”
Section: Protection In Pre-clinical Modelsmentioning
confidence: 89%
“…Furthermore, Pérez et al constructed an MVA-ZIKV vaccine expressing the prME gene, which is capable of expressing Virus-Like Particles (VLPs) and inducing partial protection in mice after a ZIKV challenge, upon a homologous prime-boost approach [21]. Of particular interest, an MVA vaccine expressing the non-structural protein 1 (NS1) of ZIKV has been demonstrated to be 100% effective in both a single-or two-dose vaccination [22]. Here, we developed four MVA-ZIKV vaccines expressing the envelope gene, with or without its transmembrane domain, both in the presence and absence of the prM antigens.…”
Section: Discussionmentioning
confidence: 99%